Human capital structure upgrading and corporate fraud: Evidence from China - Hou, Canran; Liu, Huan (International review of economics & finance, 2025)
Based on the background that China raises education expenditure, this paper proposes the concept of human capital structure upgrading and focuses on the corporate governance effect of highly educated employees on corporate fraud. Empirical results show that higher human capital structure upgrading is negatively related to corporate fraud, conclusions are robust after considering endogeneity concerns, alternative measures, and longer forecasting window. Further, this paper uses the fraud triangle theory to explain influencing mechanisms and confirms that human capital structure upgrading reduces manager's incentive, opportunity, and self-rationalization to commit fraud by easing financing constraints, increasing analyst coverage, and raising managerial salary, respectively. Research on driving force of human capital structure upgrading shows that increased proportion of senior talents is the determinant factor leading to more efficient regulation on corporate fraud. This paper can not only reveal the internal mechanism of employee governance participation, but also provide theoretical basis for enterprises to rationally optimize resource allocation and improve utilization efficiency of talents.